The Bletchley circle. [Series 1], San Francisco [videorecording (DVD)] - Balint, Crystal; Stirling, Rachael, 1977-; Graham, Julie, 1965- (BBC Studios, 2019)
A pair of British female codebreakers formerly at Bletchley Park help American cryptographers solve murders overlooked by the police in San Francisco.